Answers

2014-11-28T11:45:09+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
(Sin 5x + Sin 3 x) / ( Cos 5 x + Cos 3x )
  =  (2 Sin (5x+3x)/2 * Cos (5x-3x)/2 ) / 2 Cos (5x+3x)/2  *  Cos (5x-3x)/2
  =  Sin 4x Cos x / Cos 4x Cos x
 = tan 4x

1 5 1
2014-11-28T15:45:15+05:30
(Sin 5x+Sin 3 x)
(Cos 5x+Cos 3x)

  =  2 Sin (5x+3x × Cos (5x-3x)
               2                    2     
     2 Cos (5x+3x)×Cos (5x-3x)
                2                 2

  =  Sin 4x Cos x
     Cos 4x Cos x

 = Sin 4x
    Cos 4x

 = tan 4x
0